Pengaruh Modal Kerja, Harga Ikan Dan Hasil Tangkapan Ikan Terhadap Tingkat Pendapatan Nelayan Di Dusun 3 Bagan Kuala Serdang Bedagai - Kurniati, Toiba; Sugianto, Sugianto; Fadhila Rahma, Tri Inda (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2022)
The level of fishermen's income significantly affects the pattern of life of fishermen, the low level of productivity affects the amount of fishermen's income so that it affects the level of income earned. The low level of fishermen's welfare is a challenge in achieving the goals of fisheries development, including increasing the welfare of fishermen, fish farmers and other coastal communities. Fishing communities whose lives depend on the potential management of fishery resources. However, the visible reality is that the problem of poverty still plagues some coastal communities so that the facts that emerge are social facts that seem ironic in the midst of the abundant wealth of coastal and oceanic resources. Based on the background above, it is necessary to review 1) Does working capital affect fishermen's income? 2) Does the price of fish affect fishermen's income? 3) Does the catch of fish affect the income of fishermen? 4) Do working capital, fish prices and fish catch simultaneously affect fishermen's income? This research was conducted in Dusun 3, Bagan Village, Kuala Serdang Bedagai. The study used a causal associative quantitative research method by distributing questionnaires to 50 respondents. The sampling technique in this study was simple random sampling with multiple linear regression analysis. The results of this study indicate that partially working capital, fish prices and fish catches have a significant effect on income levels in Dusun 3 Bagan Kuala Serdang Bedagai because the significant value is less than 0.05 (<0.05). In this study, the significant value of working capital was 0.001, fish price was 0.012 and fish catch was 0.000 and the effect of working capital variable partially on income level was 36.1%, fish price variable was 26.1% and fish catch variable was 54. 9%. Then simultaneously the variables of working capital, fish prices and fish catches have a significant effect on the level of fishermen's income in Dusun 3 Bagan Kuala Serdang Bedagai with a significant value of 0.00 <0.05 and a decrease coefficient value (R2) of 0.549 or 54.9 %.